A new ismarid wasp (Hymenoptera, Diaprioidea) from mid-Cretaceous Kachin amber - Chemyreva, Vasilisa G.; Rasnitsyn, Alexandr P. (Zootaxa, 2025)
The first undoubted discovery of a parasitoid ismarid wasp from Cenomanian Kachin amber is presented here. A new genus and species, Thyburia christophi gen. et sp. nov., is described and illustrated, based on a female holotype. The family Ismaridae is synonymised with the family Diapriidae and is considered here as the subfamily Ismarinae. The taxonomy of ismarids and the diagnosis of the subfamily Ismarinae are clarified and discussed.